Koordinasi Antar Instansi Terkait Dalam Pelaksanaan Pembangunan di Daerah - Akmal, Akmal (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2006)
The main objectives ofÂ Â this research are to describe: (1) the identification and implementation of mechanism model of local bureaucracy, (2) how the condition of coordination between related bureaucracy institution. This research is descriptive, that is, to answer the details of social phenomena according to research questions. The data in this research is analyzed with qualitative analysis. The result indicated that (1) Some used of the formula are, for example: (1) coordination of authority, (2) coordination of consensus, (3) coordination of recommended work, (4) coordination of forum. The implementation and execution is coordination between related bureaucracy institutions, especially in the area of development execution. Coordination between the related institution in the province level and sub-province area has not in good implementation. Kata kunci : Koordinasi , Instansi, Pembangunan, Demokrasi